Host Species and Geography Differentiate Honeybee Gut Bacterial Communities by Changing the Relative Contribution of Community Assembly Processes - Yuan Ge (American Society for Microbiology, 2021)
Honeybees provide crucial pollination services and valuable apiarian products. The symbiotic intestinal communities facilitate honeybee health and fitness by promoting nutrient assimilation, detoxifying toxins, and resisting pathogens.